Analysis of an intermittent mechanical vapor recompression evaporation system. (5th July 2021) - Han, Dong; Si, Zetian; Chen, Junjie
Graphical abstract: Highlights: An intermittent mechanical vapor recompression system was developed. The working mechanisms were revealed through numerical simulation. An experimental study was conducted through a pilot-scale test facility. The startup time of 240 s was attained. The specific heating energy consumption of 103.2 kWh/t was attained. Abstract: This paper proposed a novel evaporation system suitable for the intermittent evaporation occasions, in which steam accumulator was applied to achieve the intermittent startup process, while mechanical vapor recompression technology was introduced to reduce energy consumption by recovering the latent heat of secondary steam in the stable evaporation process. Mathematical models were first established based on the mass and energy conservation equations, working mechanisms were revealed through numerical simulation. Besides, a pilot-scale test facility was built to validate the feasibility of the proposed system. The results showed that raising evaporation rate of the boiling pot, liquid height of the steam accumulator, and heat transfer temperature difference of the heat exchanger increased the compressor power, but raising compressor inlet pressure decreased the compressor power. Furthermore, the startup time was obtained as about 240 s via a series of experiments with pure water as feed, at the conditions of evaporation rate of 200 kg/h and evaporation temperature of 373.15 K. The specific heating energy consumption was 103.2 kWh/t, which was expected to save 73.86% energy compared to the single-effect evaporation system. Finally, economic and environmental considerations must be included, which proved that the proposed system is beneficial for the intermittent evaporation occasions.